(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Artificial Intelligence (AI) is transforming modern education, especially foreign language learning. AI-powered technologies provide learners with personalized instruction, instant feedback, and interactive communication opportunities. This article examines the impact of AI on English language acquisition, discussing both its benefits and challenges in educational environments.